Analisis Pola Spasial Persebaran Industri Kecil Menengah di kota Surabaya - Sifa Olifia Zaini Saputri; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Small and medium industries (SMIs) and medium-scale industries are sectors that contribute significantly to economic growth in the city of Surabaya. The development of the industrial sector can increase economic activities while also creating employment opportunities for the community. The distribution of industries in each area of Surabaya shows different characteristics influenced by accessibility, supporting facilities, and proximity to economic activity centers. This study aims to analyze the spatial distribution patterns of small and medium industries as well as medium-scale industries in Surabaya. The research method used is descriptive quantitative with a Geographic Information System (GIS) approach. The research data were obtained from industrial location and quantity data based on districts. The results indicate that industrial distribution tends to be concentrated in areas with good transportation networks and high economic activity. In addition, several regions have a higher level of industrial concentration compared to other areas. Infrastructure and ease of access are the main supporting factors influencing industrial development in Surabaya. This study is expected to provide recommendations for the government in developing industrial areas and improving urban spatial planning more evenly.